Chitosan/ferrous oxide nanocomposite for the sunlight-driven photocatalytic degradation of organic azo dye in aqueous solutions and aquaculture effluents wastewater - Ahmed E. Alprol; Ahmed Bakr; Sameerah I. Al-Saeedi; Abdallah Tageldein Mansour; Ehab El-Haroun; Maymounah N. Alharthi; Mohamed Ashour (Scientific Reports)
Abstract The current work presents a novel and sustainable approach that uses the synthesized Chitosan/Ferrous Oxide Nanocomposite (CFON) to remove the organic azo dye, Acid Red 73 (AR73), a hazardous pollutant commonly found in industrial wastewater, from aqueous solutions and aquaculture effluents wastewater. The CFON exhibited excellent photocatalytic degradation performance under sunlight irradiation. Batch adsorption experiments were conducted to investigate the influence of various parameters on the removal efficiency of the dye, including pH, contact time, adsorbent dosage, initial concentration, and temperature. The results showed that the nanocomposite effectively achieved a maximum removal percentage of 99.3% under optimal conditions (pH 5 for 180 min at 80 and 100 mg with 75 mg L-1 and 30 °C). Kinetic studies revealed that the adsorption process followed a pseudo-second-order model, indicating that chemisorption is the dominant mechanism. The impact of different light sources on dye removal efficiency was evaluated, confirming the superior performance of sunlight-driven photocatalysis. The application of CFON to improve water quality in aquaculture was investigated and showed effectively reduced conductivity, total dissolved solids, turbidity, and nitrate levels, demonstrating its potential for sustainable water management. This work highlights the promising potential of CFON as an environmentally friendly and efficient material to remove AR73 and improve aquaculture wastewater quality.